Influence of Social Media on Court Decisions in Blasphemy Cases: (Case Study: Putusan PN PALEMBANG Nomor 726/Pid.Sus/2023/PN Plg) - Zulaikha, Almira Novia (Faculty of Law, Universitas Jambi, 2024)
This research aims to conduct an in-depth analysis of the influence of social media on judges' decisions in religious blasphemy cases in Indonesia. In the context of the digital era, social media has become the main arena where public opinion is expressed, discussions develop, and information spreads quickly. Cases of religious blasphemy often create waves of controversy and debate on social media, widening their impact in society. This research uses a qualitative approach to analyze how social media influences the judicial process, from its role in shaping public opinion to its possible influence on arguments presented in court. Through analysis of social media content and a study of significant religious blasphemy cases, this research aims to understand the extent to which opinions and pressure generated by social media can influence judges' decisions. It is hoped that the results of the analysis will provide a deeper understanding of the challenges faced by the justice system in facing the pressures and expectations of an increasingly dominant digital space, as well as provide a basis for improving justice policies and practices that are more adaptive to social and digital dynamics.